Response to commentators - Levy, N (Taylor and Francis, 2023)
This paper replies to the contributors to a symposium on the book Bad Beliefs. It groups the criticisms and concerns of the contributors under the headings “Gaps and Holes”, “Rationality”, “Epistemic Virtue”, “Agency and Control” and “Nudges”. It defends the view that bad belief formation and maintenance is very importantly rational, though it also acknowledges gaps, limitations and unanswered questions.